Effect of imagery and heart rate variability biofeedback training on selected soccer skills performance / Sara Majlesi - Sara , Majlesi (2021)
The present study aimed to evaluate the influence of PETTLEP video imagery (Physical, Environment, Task, Timing, Learning, Emotion and Perspective), heart rate variability biofeedback (HRVB), and concurrent intervention of both on selected soccer skill performances. The objective of this study was to evaluate the effect of PETTLEP video imagery, HRVB and concurrent intervention on soccer players' reactive motor skill test (RMST), sprint time, reactive agility, passing time, and passing accuracy. Participants of this study were Malaysian high school soccer players (N=64), with mean age of 15.31±1.83, who were assigned randomly into four groups: three experimental groups and one control group. Each group had 16 players who were assigned randomly through the fishbowl method. Method: A Pre-test and Post-test design were used in this study to evaluate the effect of interventions on the players' skill performance. The three experimental groups received PETTLEP video imagery, HRVB, and concurrent (HRVB + PETTLEP video imagery) training for eight weeks in addition to their regular soccer training, while the control group only attended their regular soccer training. The experiments developed in this study consisted of a 10-minute PETTLEP video imagery training for imagery group, a 10-minute breathing exercise using the Elite HRVB app to feedback players' breathing to 5.5-6 BPM resonant breathing for HRVB group, and a 5- minute HRVB training using Elite HRVB app and a 5-minute PETTLEP video imagery training right after HRVB training for the concurrent training group. After the eight weeks of training was completed, the RMST test was administered to all participants to measure the changes in their RMST, sprint time, reactive agility, passing time, and passing accuracy. The data were analyzed with a factorial MANOVA test to evaluate the differences within and between groups. Results: Five research hypothesis of the study were supported, and statistically significant effects of experimental training on players' performance were demonstrated among all groups and within the groups. Statistically significant differences were observed between the pre-tests and the post-tests, p < .001 among all groups. The multivariate results were statistically significant differences between and within groups and also there was a statistically significant interaction effect between tests and groups of intervention on the combined dependent variables, F(15, 154.993) = 20.280, p < .001, Wilks' Λ = .050. Furthermore, the univariate interaction effects results showed all the dependent variables have statistically significant differences individually between and within groups. There was a statistically significant interaction effect between tests and type of intervention for RMST, F(3, 60) = 100.593, p = 0.001, sprint time, F(3, 60) = 42.678, p = 0.001, Reactive Agility, F(3, 60) = 173.644, p = 0.001, passing time, F(3, 60) = 34.868, p = 0.001, and Passing Accuracy, F(3, 60) = 21.018, p = 0.001. The interaction between test and type of interventions showed that 3 different types of intervention in this study were effective on each RMST component improvement differently. The Pre-test-Post-test results showed that RMST, reactive agility, passing time, and passing accuracy were statistically different within groups except for the sprint time, which was not significant in the imagery group while it was significant in other groups. The findings of this study provide evidence that eight weeks of imagery, HRVB, and concurrent interventions significantly improved soccer players' RMST, sprint time, reactive agility, passing time, and passing accuracy test results. However, concurrent intervention group showed greater improvement than the other groups, followed by the HRVB intervention group and PETTLEP video imagery group.